Análise econômica sobre simulações de fusões no mercado brasileiro de carros populares - ano 2007 - Silva Junior, Rosendo Fernandes da (2008)
This dissertation presents descriptive analysis of mergers’simulation on the brasilian market of popular cars in 2007. The model measure effects in prices just to gain synergy, and in quality the output. To enfeeble an assumption of marginal costs constant in the models pré and pós-merger, typically used in the others models of the several sectors. In the scope of the industrial empirical economic, models of prices’prevision pós-merger are desirable. It´s used, computing skills of calibration in search of maximum profit in equilibrium on the firms to related with the application in market. Initially, a brief history of automobilistic national market is presented. The data set is composed of total of unit sent in 2007, the price of represent model, market share in unit and market share in value and the total market of popular cars. From this information it was possible to measure variables of economic significance such as price, quality, market power and profits of companies in this segment. The methodology is applied to the calibration of parameters of a structural model of demand and supply. On the demand side, the traditional LOGIT model is assumed. In turn, on the supply side it is assumed that firms compete à la Bertrand.